2020
DOI: 10.1002/aqc.3397
|View full text |Cite
|
Sign up to set email alerts
|

Common hippopotamus in Nigeria: New census data and literature review confirm the conservation importance of sites outside protected areas

Abstract: 1. Once abundant across Africa, the common hippopotamus is threatened owing to habitat degradation and loss, hunting, and negative human-wildlife interactions. West African populations are notably small and fragmented and therefore at greatest risk. 2. In Nigeria, Africa's most populous nation, the IUCN estimates that only 100 hippos remain. They occur in protected areas, such as national parks and game reserves, and outside protected areas in estuarine habitats, inland rivers, lakes, and reservoirs. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…For example, Stears et al (2021) observed hippo aggregation in a few remaining pools in response to drought in Tanzania. In such contexts, dammed and impounded water may provide important refugia for hippos when pooled water becomes limited (Baker et al, 2020; Utete et al, 2017). However, increased aggregation during drought can have dramatic consequences for water quality and aquatic ecology within pools and downstream (Dutton et al, 2018; Subalusky et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Stears et al (2021) observed hippo aggregation in a few remaining pools in response to drought in Tanzania. In such contexts, dammed and impounded water may provide important refugia for hippos when pooled water becomes limited (Baker et al, 2020; Utete et al, 2017). However, increased aggregation during drought can have dramatic consequences for water quality and aquatic ecology within pools and downstream (Dutton et al, 2018; Subalusky et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, human exploitation of hippos and their habitat is responsible for their population decline in many areas (Lewison, 2007; Zisadza et al ., 2010; Kanga et al ., 2012; Scholte & Iyah, 2016; Utete, 2020). Hippos often venture outside protected areas because their aquatic habitats render fences less restrictive to their movements, making hippos more prone to encounters with people than many other large mammals (Mackie, Dunham & Ghiurghi, 2013; Post, 2017; Baker et al ., 2020). Furthermore, hippos venturing into human‐inhabited landscapes, often referred to as ‘problem animals’, are routinely shot and killed (Mkanda, 1994; Chomba et al ., 2012; Utete, 2020) without much consideration for their vulnerable conservation status (Lewison & Pluháček, 2017).…”
Section: Hippo Conservation and Human Influences On Hippo Ecosystem E...mentioning
confidence: 99%
“…Human-Hippo conflict denotes any instance in which the resource demands of humans and Hippos overlap, spurring competition for food, space, and water and thus creating tension between people and Hippos (Messmer, 2000;Seoraj-Pillai & Pillay, 2017). Hippopotamus (Hippopotamus amphibious) are among Africa's most destructive crop raiders (Lamarque et al, 2009;Baker et al, 2020). In Adamawa state, while the exact population of Hippopotamus in the riverine communities is not exactly known, (Baker et al2020) it is estimated to be about 45 animals around Kiri dam reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…During this time, hippos may travel long distances in search of new water sources or better grazing areas. As they move, they may come into contact with human settlements, which can lead to human-wildlife conflicts and potential attacks (Baker et al, 2020). HWC (human-wildlife conflict) is fast becoming a critical threat to the survival of many globally endangered species (Distefano, 2005;Cromsigt et al, 2013;Manral et al, 2016).…”
mentioning
confidence: 99%